Association Between Postpartum Depression and Sleep Quality in Pakistani Women in Peshawar, Pakistan - Zia Ul Ain Sabiha, Tayyaba Zia, Fatima Saadat, Umair Mudassar, K. Suresh Babu, Ubaidullah, Sudhair Abbas Bangash, Farwa Daar, Salman Haider, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The literature is sparse regarding the link between postpartum females and postpartum depression in low- to middle-income (LMIC) countries. This study examined the association between some self-reported sleeping rhythm alterations (from six weeks to seven months and months after giving birth) and depressive symptoms at seven months amongst women’s who were having high risk for depressive symptoms. Material and Methods: A total of 180 newly delivered mothers who were assigned to the medical facility, took part in this cross-sectional research. To judge the effectiveness of sleeping habits, the "Pittsburg Sleep Quality Index" (PSQI) questionnaire was used. To quantify depressive symptoms, we also employed the "Edinburg Postnatal Depression Questionnaire" which is also known as (EPDS). Moreover, regression analysis was used to find out the association between sleep quality and maternal depression. Result: In general, sleep - related issues are resolved in six to seven months. Nevertheless, at seven months following the birth, worsening or just modest improvement in sleep issues were linked to more severe depressive symptoms. Regarding the different types of sleep issues, high levels of depressive symptoms were associated with self-reported altered sleep delay, including such "how lengthy it ends up taking to fall asleep during the night," in during the day disturbance in features, including such "difficulties involved in staying up throughout the day," and the level of sleep, such as "qualitative rate and quality of sleep." Conclusion: Usually, throughout the postpartum period, sleep issues go better. However, the prevalence of depression was high and the poor quality of sleep was identified. In Pakistan, the positive association between depression and poor sleep quality proposes early identification and support for women at high risk of poor quality of sleep. Women should therefore need to be knowledgeable about probable deterioration of sleep patterns and strategies for preventing insomnia disorders before visiting the clinic at six weeks postpartum. Keywords: postpartum, sleep issues, PSQI, EPDS, Peshawar.